The Prenatal Origins of Human Brain Asymmetry: Lessons Learned from a Cohort of Fetuses with Body Lateralization Defects. (27th March 2021) - Kienast, Patric; Schwartz, Ernst; Diogo, Mariana C; Gruber, Gerlinde M; Brugger, Peter C; Kiss, Herbert; Ulm, Barbara; Bartha-Doering, Lisa; Seidl, Rainer; Weber, Michael; Langs, Georg; Prayer, Daniela; et al.
Abstract: Knowledge about structural brain asymmetries of human fetuses with body lateralization defects—congenital diseases in which visceral organs are partially or completely incorrectly positioned—can improve our understanding of the developmental origins of hemispheric brain asymmetry. This study investigated structural brain asymmetry in 21 fetuses, which were diagnosed with different types of lateralization defects; 5 fetuses with ciliopathies and 26 age-matched healthy control cases, between 22 and 34 gestational weeks of age. For this purpose, a database of 4007 fetal magnetic resonance imagings (MRIs) was accessed and searched for the corresponding diagnoses. Specific temporal lobe brain asymmetry indices were quantified using in vivo, super-resolution-processed MR brain imaging data. Results revealed that the perisylvian fetal structural brain lateralization patterns and asymmetry indices did not differ between cases with lateralization defects, ciliopathies, and normal controls. Molecular mechanisms involved in the definition of the right/left body axis—including cilium-dependent lateralization processes—appear to occur independently from those involved in the early establishment of structural human brain asymmetries. Atypically inverted early structural brain asymmetries are similarly rare in individuals with lateralization defects and may have a complex, multifactorial, and neurodevelopmental background with currently unknown postnatal functional consequences.